Motion Response on The Water Ambulance Ship - Alamsyah Alamsyah; Ardhi Hidayatullah; Suardi Suardi; Wira Setiawan; Habibi Habibi; Samsu Dlukha Nurcholik (International Journal of Marine Engineering Innovation and Research, 2023)
In designing a ship, it is necessary to know the response of the ship's motion before sailing. The purpose of this research is to determine the ship's motion response to waves as well as ship speed in ship loading operational conditions. The method used in this study is the B-spiline mathematical equation and the strip theory method, with the help of ship motion software, which varies the ship's load by 100% DWT, 50% DWT, and 25% DWT. While the highest significant amplitude heave value occurs on a ship with 100% DWT conditions with a speed of 18 knots and a wave direction of 900, which is 2.70 meters, the highest significant value of amplitude pitch occurs on a ship with a condition of 25% DWT with a speed of 6 knots and a wave arrival direction of 1800, namely 1.10 degrees, and the highest significant value of roll amplitude occurs in ships with 25% DWT conditions with speeds of 18 knots with a wave arrival direction of 900, which is 3.42 deg. The research results detected at a speed of 18 knots for the significant amplitude heave value, the significant amplitude pitch value, and the maximum RAO value still meet the Nordforsk criteria.